Preparation method of anode titanium-based porous transmission layer
The titanium fiber felt was laid dryly and the precious metal oxide film was deposited using chemical vapor deposition technology, which solved the problem of reduced conductivity in the oxidative environment of titanium materials, and realized anode titanium-based porous transport layer with corrosion resistance and strong conductivity. The service life of titanium fiber felt is extended and the process is simplified.
Patent Information
- Application Number
- CN202411591600.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, titanium materials are prone to oxidation in an oxidizing environment, resulting in a decrease in electrode conductivity, and the traditional plating process is complex and uneven.
通过干法铺制钛纤维毡并结合化学气相沉积技术,在钛纤维毡表面沉积贵金属氧化物薄膜,形成耐腐蚀、导电性强的阳极钛基多孔传输层。
It improves the corrosion resistance and conductivity of titanium fiber felt, extends its service life, simplifies process steps, and reduces environmental pollution.
Smart Images

Figure CN119465076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry and relates to a method for preparing an anode titanium-based porous transmission layer. Background Art
[0002] The proton exchange membrane (PEM) electrolyzer is mainly composed of end plates, bipolar plates, diffusion layers, catalyst layers, proton exchange membranes and gaskets. The anode titanium-based porous transport layer plays the role of water transport, exhaust, heat conduction and electrical conduction in the anode oxygen evolution reaction. It is an integration of gas, liquid, electricity and heat four-phase fluid fields. When the electrolysis reaction occurs in the PEM electrolyzer, the anode of the electrolyzer is an acidic environment, and the electrolysis voltage is usually higher than 1.6V. Therefore, in practical applications, titanium materials with good stability are usually selected: porous sintered titanium plates and titanium fiber felts. However, titanium materials without surface treatment will gradually form a layer of titanium dioxide film on the surface in an oxidizing environment, resulting in a significant reduction in electrode conductivity.
[0003] In order to solve the oxidation problem of titanium materials, electroplating, vapor deposition, magnetron sputtering and other methods are usually used to add oxidation-resistant precious metal coatings on the surface of titanium materials, such as ruthenium oxide, iridium oxide, etc. These precious metal oxides have high corrosion resistance, which can protect titanium fiber felt from corrosion in an acidic environment and increase its service life. At the same time, it has low electrical resistivity and high catalytic activity, which improves the efficiency of the catalyst in the catalyst layer, effectively reduces the loading of the catalyst layer, and improves the battery efficiency. Patent CN109518168A discloses a method for preparing an active titanium-based electrode plate with a high-stability coating, using titanium as the substrate, using a pyrolysis method to form a multi-metal catalyst layer of the titanium-based catalyst layer, and combining a sol-gel method and an electrochemical deposition method to form a dense oxide titanium-based protective layer. Patent CN114990604A discloses a diffusion layer loaded with catalysts for a PEM water electrolysis cell and a method for preparing the same. A double-layer coating layer is prepared on the diffusion layer, including a metal diffusion layer substrate, a corrosion-resistant intermediate layer and a catalytically active layer. Patent CN115125558A discloses a method for preparing a metal-based conductive porous transport layer and its application in a water electrolysis battery. A metal-based conductive material powder is scraped onto the surface of a titanium felt to obtain a metal-based conductive porous transport layer.
[0004] However, the traditional pyrolysis method of forming a coating has a weak bonding force between the coating and the substrate, and acid corrosion and other treatments are performed before plating, which makes the process cumbersome. The electrochemical deposition method of plating the metal layer has an uneven coating, large roughness, and magnetron sputtering coating on the surface of the substrate. The precious metal oxide film deposited by chemical vapor deposition (CVD) technology can not only cover the surface of the substrate, but also be deposited in the pores of the substrate.
[0005] Therefore, it is necessary to develop a new method for preparing an anode titanium-based porous transport layer with simpler process, better corrosion resistance and stronger conductivity. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an anode titanium-based porous transport layer. The prepared titanium-based porous transport layer has the characteristics of higher corrosion resistance, lower resistance, stronger conductivity, more uniform thickness, and longer service life of the titanium fiber felt.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing an anode titanium-based porous transport layer, characterized in that the specific preparation steps of the anode titanium-based porous transport layer are as follows:
[0009] S1. Titanium fiber felt is laid by dry method. The specific steps of forming titanium fiber felt are as follows:
[0010] First, the fiber bundles are combed into single fluffy fibers through air combing, and then laid in a web laying machine for forming. After being rolled by a roller press, they are placed in a vacuum sintering furnace for sintering at a temperature of 900-1500°C and a vacuum degree of ≤3×10 -2 Pa; and then perform multiple roller pressing and leveling for 2 to 3 times to obtain titanium fiber felt;
[0011] S2. Preparation of metal composite materials:
[0012] Fully dissolve the polyethylene glycol solid in anhydrous ethanol, add the coupling agent, stir in a stirrer for 0.5 to 1 hour, add the metal precursor powder after stirring evenly, stir at a low speed for 15 to 20 minutes at a speed of 100 to 150 r / min, and then stir at a high speed for 2 to 3 hours at a speed of 800 to 1200 r / min to obtain a metal slurry;
[0013] Add polyvinyl alcohol, cationic surfactant and polyaniline to metal slurry, stir thoroughly and then perform ultrasonic treatment for 0.5h, wherein the mass ratio of polyethylene glycol to anhydrous ethanol, metal precursor, cationic surfactant, coupling agent, polyvinyl alcohol and polyaniline is 2:15-20:20-25:1-2:0.5-1:0.5-1:0.5-1, react by microwave method for 5-10min, filter and dry the solid in an oven at 100°C for 2-4h to obtain the metal composite material;
[0014] S3. Preparation of titanium-based anode gas transport layer:
[0015] The titanium fiber felt is rinsed with anhydrous ethanol and deionized water, dried in an oven and placed in a chemical vapor deposition furnace, and preheated with hydrogen as a carrier gas at a temperature of 200-500°C for 10-50 minutes. The prepared metal composite material is then gasified and passed into a deposition box, and carrier gases such as carbon dioxide and hydrogen are simultaneously introduced to form an oxide metal coating on the surface of the titanium fiber felt substrate. The coating thickness is 1-30 μm, and a titanium-based anode gas transport layer is obtained after cooling.
[0016] As a preferred technical solution of the present invention, in step S1, the titanium fiber has a diameter of 10 to 30 μm and a length of 30 to 80 mm.
[0017] As a preferred technical solution of the present invention, in step S1, the titanium fiber felt has a thickness of 0.1-1.0 mm and a porosity of 50-90%, wherein the single-layer felt has a gram weight of 50-600 g / m 2 , during the rolling process, single-layer or multi-layer felt is selected for rolling forming.
[0018] As a preferred technical solution of the present invention, in step S2, the cationic surfactant is one of guar gum, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and a cationic antistatic agent.
[0019] As a preferred technical solution of the present invention, in step S2, the average molecular weight of the polyethylene glycol is 800-1200.
[0020] As a preferred technical solution of the present invention, in step S2, the coupling agent is one of a silane coupling agent, a phthalate coupling agent, a borate coupling agent, and an aluminate coupling agent.
[0021] As a preferred technical solution of the present invention, in step S2, the metal precursor is one or more halides or metal organic compounds of iridium, ruthenium, platinum, palladium, osmium, and rhodium; the chemical vapor deposition coating can be plated multiple times with different metal precursors.
[0022] As a preferred technical solution of the present invention, in step S3, the flow rate of the hydrogen used for preheating is 300-700 mL / min.
[0023] As a preferred technical solution of the present invention, in step S3, the flow rates of the hydrogen and carbon dioxide introduced simultaneously are 300-700 mL / min and 100-400 mL / min respectively; the pressure of chemical vapor deposition is 800-1200 Pa, and the temperature is 300-800°C.
[0024] Beneficial effects of the present invention:
[0025] (1) By adding conductive polyaniline to the metal precursor, the conductivity of the titanium-based porous transport layer is increased, so that an effective charge conduction channel exists between the titanium fiber felt and the metal oxide coating, and at the same time, the titanium passivation caused by the unfavorable charge conduction between the titanium fiber felt and the traditional metal oxide layer due to the lack of conductive substances is suppressed; at the same time, the addition of cationic surfactants makes the metal organic ions better dispersed in the organic solvent and increases the number of charges therein, which further increases the charge transfer between the titanium fiber felt and the surface coating. The addition of a coupling agent allows each component to exist stably and improves the adhesion between the coating and the titanium fiber felt.
[0026] (2) The porous titanium felt is prepared by the titanium fiber airflow felting molding technology, and then a layer of precious metal film is deposited on the surface of the titanium fiber by chemical vapor deposition technology to improve the corrosion resistance and oxidation resistance of the titanium fiber felt. At the same time, a mixture of carbon dioxide and hydrogen is introduced to prevent the titanium fiber felt from being oxidized, reduce the risk of the oxide metal coating falling off, and ensure that the titanium fiber felt has high conductivity and a high number of active sites, thereby improving the catalytic efficiency. In addition, the dry method used to lay the titanium fiber felt saves water resources, while reducing the acid pretreatment process in the traditional preparation of the titanium-based diffusion layer, simplifying the process steps, and reducing environmental pollution. Moreover, the chemical vapor deposition technology is used to prepare the precious metal oxide film, which has the properties of high dispersion, high coverage, high purity, low resistance, and uniform particle size and strong bonding with the substrate, which improves the unevenness of the platinum coating of the anode titanium-based diffusion layer in the traditional PEM electrolytic cell, expands the active sites, and the catalytic coating can catalyze the electrode reaction, reducing the amount of catalyst in the catalytic layer. The dense precious metal oxide films such as iridium oxide or ruthenium oxide formed by chemical vapor deposition are more corrosion-resistant and can enhance the life of titanium fiber felt. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0028] Figure 1 Polarization curves of the anode gas transport layers prepared in the examples and comparative examples after assembling the electrolytic cell. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] Example 1
[0031] Titanium fiber felt is laid by dry method. The specific forming steps of titanium fiber felt are as follows:
[0032] Titanium fibers with a diameter of 15 μm and a length of 50 mm were used. After being air-combed, they were formed in a web laying machine, pressed and reinforced by a roller press, and then sintered in a vacuum sintering furnace. The sintering temperature was 1200 °C and the vacuum degree was 2 × 10 -2 Pa; then the titanium fiber felt is rolled and flattened to obtain a titanium fiber felt with a thickness of 0.23 mm and a porosity of 85%;
[0033] Preparation of metal composite materials:
[0034] Fully dissolve 2g of polyethylene glycol solid in 20g of anhydrous ethanol, add 1g of coupling agent, stir thoroughly in a stirrer for 0.5-1h, stir evenly, add 20g of metal organic precursor iridium hexafluoride (IrF6) powder, stir at low speed for 20min, the speed is 150r / min; then stir at high speed for 3h, the speed is 1200r / min; obtain metal slurry;
[0035] 1 g of polyvinyl alcohol, 1 g of cationic surfactant and 1 g of polyaniline were added to the metal slurry, and the mixture was fully stirred and then subjected to ultrasonic treatment for 0.5 h, reacted by microwave method for 10 min, filtered, and dried in an oven at 100° C. for 3 h to obtain the treated IrF6 precursor;
[0036] Preparation of titanium-based anode gas transport layer:
[0037] The titanium fiber felt was rinsed with anhydrous ethanol and deionized water and placed in a chemical vapor deposition furnace after drying. The carrier gas H2 was introduced for preheating with a hydrogen flow rate of 400 mL / min. The mixture was kept at 400°C for 30 min. The treated IrF6 was then vaporized and introduced into a deposition box. At the same time, carrier gases carbon dioxide and hydrogen were introduced with a hydrogen flow rate of 400 mL / min and a carbon dioxide flow rate of 300 mL / min. The pressure in the deposition box was 700 Pa and the temperature was 700°C. An oxide metal coating was formed on the surface of the titanium fiber felt substrate with a coating thickness of 20 μm. A titanium-based anode gas transport layer IrO2@titanium fiber felt was obtained, and the final IrO2@titanium fiber felt was 0.25 mm.
[0038] Example 2
[0039] Titanium fiber felt is laid by dry method. The specific forming steps of titanium fiber felt are as follows:
[0040] Titanium fibers with a diameter of 20 μm and a length of 50 mm were used. After being air-combed, they were formed in a web laying machine, pressed and reinforced by a roller press, and then sintered in a vacuum sintering furnace. The sintering temperature was 1300 °C and the vacuum degree was 2 × 10 -2 Pa; then the titanium fiber felt is rolled and flattened to obtain a titanium fiber felt with a thickness of 0.23 mm and a porosity of 85%;
[0041] Preparation of metal composite materials:
[0042] Dissolve 2g of polyethylene glycol solid in 20g of anhydrous ethanol, add 1g of coupling agent, stir in a stirrer for 0.5-1h, stir evenly, add 20g of metal organic precursor ruthenium hexafluoride (RuF6) powder, stir at low speed for 20min, the speed is 150r / min; then stir at high speed for 3h, the speed is 1200r / min; obtain metal slurry;
[0043] 1 g of polyvinyl alcohol, 1 g of cationic surfactant and 1 g of polyaniline were added to the metal slurry, and the mixture was fully stirred and then ultrasonically treated for 0.5 h, reacted by microwave method for 10 min, filtered, and dried in an oven at 100° C. for 3 h to obtain the treated RuF6 precursor;
[0044] Preparation of titanium-based anode gas transport layer:
[0045] The titanium fiber felt was rinsed with anhydrous ethanol and deionized water and placed in a chemical vapor deposition furnace after drying. Hydrogen carrier gas was introduced for preheating at a hydrogen flow rate of 400 mL / min and the temperature was kept at 400°C for 30 minutes. The treated RuF6 was then vaporized and introduced into a deposition box. Carbon dioxide and hydrogen carrier gases were introduced at the same time. The hydrogen flow rate was 400 mL / min and the carbon dioxide flow rate was 300 mL / min. The pressure of the deposition box was 700 Pa and the temperature was 750°C. An oxide metal coating was formed on the surface of the titanium fiber felt substrate with a coating thickness of 20 μm. A titanium-based anode gas transport layer RuO2@titanium fiber felt was obtained. The final RuO2@titanium fiber felt was 0.25 mm.
[0046] Example 3
[0047] Titanium fiber felt is laid by dry method. The specific forming steps of titanium fiber felt are as follows:
[0048] Titanium fibers with a diameter of 20 μm and a length of 50 mm are used. After being air-combed, they are formed in a web laying machine, pressed and reinforced by a roller press, and then sintered in a vacuum sintering furnace. The sintering temperature is 1200 °C and the vacuum degree is 2×10 -2 Pa; then the titanium fiber felt is rolled and flattened to obtain a titanium fiber felt with a thickness of 0.37 mm and a porosity of 80%;
[0049] Preparation of metal composite materials:
[0050] Fully dissolve 2g of polyethylene glycol solid in 20g of anhydrous ethanol, add 1g of coupling agent, stir thoroughly in a stirrer for 0.5-1h, stir evenly, add 20g of metal organic precursor iridium hexafluoride (IrF6) powder, stir at low speed for 20min, the speed is 150r / min; then stir at high speed for 3h, the speed is 1200r / min; obtain metal slurry;
[0051] 1 g of polyvinyl alcohol, 1 g of cationic surfactant and 1 g of polyaniline were added to the metal slurry, and the mixture was fully stirred and then subjected to ultrasonic treatment for 0.5 h, reacted by microwave method for 10 min, filtered, and dried in an oven at 100° C. for 3 h to obtain the treated IrF6 precursor;
[0052] Preparation of titanium-based anode gas transport layer:
[0053] The titanium fiber felt is rinsed with anhydrous ethanol and deionized water and placed in a chemical vapor deposition furnace after drying. The carrier gas H2 is introduced for preheating at a flow rate of 400 mL / min and a temperature of 200-500°C for 10-50 min. The treated IrF6 is then vaporized and introduced into a deposition box. At the same time, carrier gases carbon dioxide and hydrogen are introduced, with a hydrogen flow rate of 400 mL / min and a carbon dioxide flow rate of 300 mL / min. The deposition box pressure is 700 Pa and the temperature is 600°C. An iridium oxide coating is formed on the surface of the titanium fiber felt substrate with a coating thickness of 30 μm. A titanium-based anode gas transport layer IrO2@titanium fiber felt is obtained, and the final IrO2@titanium fiber felt is 0.40 mm.
[0054] Comparative Example 1
[0055] Titanium fibers with a diameter of 20 μm and a length of 50 mm are used. After being air-combed, they are formed in a web laying machine, pressed and reinforced by a roller press, and then sintered in a vacuum sintering furnace. The sintering temperature is 1200 ° C and the vacuum degree is 2×10 -2 Pa; then roll-press and flatten the titanium fiber felt to a thickness of 0.37 mm and a porosity of 80%;
[0056] The titanium fiber felt was first cleaned with a methanol solution, then immersed in a 15% oxalic acid solution for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt was neutral, and finally dried to obtain a titanium fiber felt substrate to be deposited;
[0057] Prepare conductive metal slurry: take 2g of phenolic resin and 1g of dispersant and completely dissolve them in 30g of isopropanol, then add 35g of iridium powder, stir and disperse them evenly to obtain conductive metal slurry containing iridium powder;
[0058] The slurry containing iridium powder is scraped onto the pretreated titanium fiber felt, and then dried in an oven at a temperature of 120° C. for 1 hour to obtain a titanium fiber felt containing an iridium coating.
[0059] according to Figure 1 It can be concluded that the polarization curve of Example 1 has the most gentle trend and the lowest slope. The greater the maximum current density, the better the power performance of this battery. The slope of the polarization curve of Comparative Example 1 is the largest, indicating that the porous transport layer prepared by the present invention has good performance when used to form a proton exchange membrane fuel cell.
[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an anode titanium-based porous transport layer, characterized in that: The specific preparation steps of the anode titanium-based porous transport layer are as follows: S1. Titanium fiber felt is laid by dry method. The specific steps of forming titanium fiber felt are as follows: First, the fiber bundles are combed into single fluffy fibers through air combing, and then laid in a web laying machine for forming. After being rolled by a roller press, they are placed in a vacuum sintering furnace for sintering at a temperature of 900-1500°C and a vacuum degree of ≤3×10 -2 Pa; and then perform multiple roller pressing and leveling for 2 to 3 times to obtain titanium fiber felt; S2. Preparation of metal composite materials: Fully dissolve the polyethylene glycol solid in anhydrous ethanol, add the coupling agent, stir in a stirrer for 0.5 to 1 hour, add the metal precursor powder after stirring evenly, stir at a low speed for 15 to 20 minutes at a speed of 100 to 150 r / min, and then stir at a high speed for 2 to 3 hours at a speed of 800 to 1200 r / min to obtain a metal slurry; Add polyvinyl alcohol, cationic surfactant and polyaniline to metal slurry, stir thoroughly and then perform ultrasonic treatment for 0.5h, wherein the mass ratio of polyethylene glycol to anhydrous ethanol, metal precursor, cationic surfactant, coupling agent, polyvinyl alcohol and polyaniline is 2:15-20:20-25:1-2:0.5-1:0.5-1:0.5-1, react by microwave method for 5-10min, filter and dry the solid in an oven at 100°C for 2-4h to obtain the metal composite material; S3. Preparation of titanium-based anode gas transport layer: The titanium fiber felt is rinsed with anhydrous ethanol and deionized water, dried in an oven and placed in a chemical vapor deposition furnace, and preheated with hydrogen as a carrier gas at a temperature of 200-500°C for 10-50 minutes. The prepared metal composite material is then gasified and passed into a deposition box, and carrier gases such as carbon dioxide and hydrogen are simultaneously introduced to form an oxide metal coating on the surface of the titanium fiber felt substrate. The coating thickness is 1-30 μm, and a titanium-based anode gas transport layer is obtained after cooling.
2. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S1, the titanium fiber has a diameter of 10 to 30 μm and a length of 30 to 80 mm.
3. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S1, the titanium fiber felt has a thickness of 0.1-1.0 mm and a porosity of 50-90%, wherein the weight of a single layer of felt is 50-600 g / m 2 , during the rolling process, single-layer or multi-layer felt is selected for rolling forming.
4. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S2, the cationic surfactant is one of guar gum, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and a cationic antistatic agent.
5. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S2, the average molecular weight of the polyethylene glycol is 800-1200.
6. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S2, the coupling agent is one of a silane coupling agent, a phthalate coupling agent, a borate coupling agent, and an aluminate coupling agent.
7. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S2, the metal precursor is one or more of iridium, ruthenium, platinum, palladium, osmium, rhodium halides or metal organic compounds; the chemical vapor deposition coating can be plated multiple times with different metal precursors.
8. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S3, the flow rate of the hydrogen used for preheating is 300-700 mL / min.
9. The method for preparing an anode titanium-based porous transport layer according to claim 1, characterized in that: In step S3, the flow rates of the hydrogen and carbon dioxide introduced simultaneously are 300-700 mL / min and 100-400 mL / min respectively; the pressure of chemical vapor deposition is 800-1200 Pa, and the temperature is 300-800° C.
Citation Information
Patent Citations
Preparation method of activated titanium-based electrode plate with high-stability coating
CN109518168A
Catalyst-loaded diffusion layer for PEM water electrolysis cell and preparation method of catalyst-loaded diffusion layer
CN114990604A
Preparation method of metal-based conductive porous transmission layer and application of metal-based conductive porous transmission layer in electrolytic water battery
CN115125558A
Corrosion-resistant coating, modified titanium material and preparation method and application of modified titanium material
CN117779002A
Method for manufacturing negative electrode active material for use in non-aqueous electrolyte secondary battery, negative electrode material for use in non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
EP2509139A1